(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate limb salvage outcomes and identify factors associated with major amputation in diabetic foot patients undergoing below-the-knee endovascular revascularization. Subjects and methods: A single-center prospective observational study was conducted on 149 type 2 diabetic patients with foot ulcers and below-the-knee arterial lesions (occlusion or ≥70% stenosis) who underwent endovascular intervention at University Medical Center Ho Chi Minh City from January 2020 to December 2024. Outcome measures included limb salvage rate, primary patency, ulcer healing, hemodynamic improvement, complications, and factors associated with major amputation at 6 months. Results: The mean age was 67.5 ± 9.7 years, and 66.4% of patients were male. WIfI stage 3 accounted for 31.5% of cases. At 6 months, the limb salvage rate was 87.2%, primary patency was 84.6%, and ulcer healing was achieved in 73.2% of patients. The ankle–brachial index improved from 0.78 ± 0.21 to 0.95 ± 0.18 (p<0.001). Multivariable analysis identified WIfI stage 3 (OR 3.52; 95% CI 1.69–7.32; p=0.001), poor distal runoff (OR 2.92; 95% CI 1.35–6.31; p=0.006), and severe vascular calcification (OR 2.61; 95% CI 1.21–5.63; p=0.014) as factors independently associated with major amputation. The major complication rate was 1.3%, and no procedure-related mortality was observed. Conclusion: Below-the-knee endovascular intervention is a safe and effective strategy for limb salvage in patients with diabetic foot disease. WIfI classification, distal runoff status, and vascular calcification were independently associated with major amputation and should be systematically evaluated before intervention to support risk stratification and treatment planning.